Млекопитающие - Травина Ирина Владимировна (Детская энциклопедия, 2018)
Экземпляры: ДБ (20231114ԁ) / Инвентарный номер: 65568 / Цена: 50.00 / Сис.шифр: 28.693я2мл / Авт.знак: М 72 / ГРНТИ: 34.33 / ББК: 28.693я2мл